THE INFLUENCE OF STUDENTS’ HABITS IN WATCHING TIKTOK ENGLISH CONTENT ON VOCABULARY ENHANCEMENT OF ENGLISH EDUCATION STUDENTS AT SRIWIJAYA UNIVERSITY - Tri Ambarwati; Zuraida Zuraida (TELL - US JOURNAL, 2025)
This study investigates the influence of students’ habits in watching TikTok English content on vocabulary enhancement among English Education students at Sriwijaya University. The objective is to determine whether students’ frequent engagement with TikTok contributes significantly to their vocabulary development and to identify the types of English content that are perceived as most effective in improving vocabulary mastery. The research applied an associative quantitative design within the positivism paradigm. The population consisted of 132 second- and fourth-semester students of the English Education Study Program at Sriwijaya University during the 2024/2025 academic year, selected using a saturated sampling technique. Data were collected through a validated and reliable questionnaire distributed via Google Forms, and analyzed using simple linear regression with SPSS, supported by descriptive statistics and classical assumption tests. The findings revealed a strong and positive relationship between students’ habits in watching TikTok English content and their vocabulary enhancement, with a regression coefficient of 0.809 and a significance value of 0.000 (<0.05). The coefficient of determination (R² = 0.707) indicated that 70.7% of students’ vocabulary enhancement was influenced by their habits of watching TikTok English content, while the remaining 29.3% was affected by other factors. Descriptive analysis further showed that the types of TikTok English content most effective in enhancing vocabulary were educational-entertainment videos, daily conversations, and idioms or slang explanations. These forms of content provide contextualized, engaging, and authentic exposure to English, supporting vocabulary acquisition in a fun and accessible way. In conclusion, the study confirms that students’ frequent exposure to TikTok English content significantly improves their vocabulary mastery. The results highlight the potential of TikTok as an innovative and enjoyable learning medium that blends education with entertainment, making it a valuable supplement to traditional classroom learning.